Curcumin-mediated exosomes from bone marrow mesenchymal stem cells inhibits ACC-M cell proliferation, migration and invasion in vitro - CHENG Hao; WU Fayin; LIU Zhidan (Kouqiang hemian waike zazhi)
[Objective:] To investigate the effect of curcumin - mediated exosomes of bone marrow mesenchymal stem cells (BMSCs) on proliferation and metastasis of ACC-M cells and its mechanism. [Methods:] After being co-cultured with 7.5 μmmol/L curcumin and BMSCs for 72 h, exosomes were isolated and identified, and co-cultured with ACC-M cells. ACC-M cells were divided into control group (normal culture), BMSC-Exo group (no curcumin-treated BMSCs exosomes co-cultured with ACC-M cells), Cur-BMSC-Exo group (curcumin-treated BMSCs exosomes co-cultured with ACC-M cells) and Cur group (7.5 μmmol/L curcumin treated cells). Western blotting was used to detect the expression of tumor susceptibility gene 101 (TSG-101), CD63, CD9 and recombinant human calnexin (CANX) proteins in exosome and the expression of E-cadherin, N-cadherin, vimentin, transforming growth factor-β1 (TGF-β1) and p-ERK proteins in ACC-M cells after 48 h of culture. The survival rate of ACC-M cells was determined by cell counting kit-8 (CCK-8) assay. The migration and invasion of ACC-M cells were detected by transwell assay. The relative expression levels of TGF-β1 and ERK mRNA in ACC-M cells were detected by real-time quantitative polymerase chain reaction(RT-qPCR) assay. [Results:] Compared with control group and BMSC-Exo group, the cell viability, cell migration and invasion number, and the expression levels of N-cadherin, vimentin, TGF-β1 and ERK were significantly decreased in Cur-BMSC-Exo and Cur groups (P<0.05), while E-cadherin protein level was significantly increased (P<0.05); compared with the Cur-BMSC-Exo group, the cell viability, cell migration and invasion numbers, and the expression levels of N-cadherin, vimentin, TGF-β1 and ERK were significantly increased in the Cur group (P<0.05), while E-cadherin protein level was significantly decreased (P<0.05). [Conclusion:] BMSCs exosomes can act as curcumin carrier to inhibit proliferation and metastasis of ACC-M cells and regulate TGF-β1/ERK signaling pathway.